2021
DOI: 10.20491/isarder.2021.1349
|View full text |Cite
|
Sign up to set email alerts
|

Örgütsel Sessizliğin İş Yerinde Mutluluk Üzerindeki Etkisi: Bir Psiko-Sosyal Bireysel Kaynak Yokluğu Olarak Umutsuzluğun Rolü (The Effect of Organizational Silence on Happiness in the Workplace: The Role of Hopelessness as a Psycho-Social Lack of Individual Resources)

Abstract: Bu çalışmada, örgütsel sessizliğin çalışanların iş yerindeki mutlulukları üzerindeki etkisinde bir psiko-sosyal kaynak yokluğu olarak umutsuzluk duygusunun aracı (mediatör) rolü incelenmektedir. Yapılan literatür araştırması sonucunda, örgütsel düzeyde meydana gelen sessizliğin, çalışanların iş yerindeki mutluluklarını ve umutsuzluk duygularını etkileyebileceği düşünülmektedir. Ayrıca, örgütsel sessizliğin iş yerinde mutluluk üzerinde etkisinde umutsuzluğun aracı değişken olarak rolünün olabileceği varsayılmak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Based on this result, it can be said that as the employees' voice increases, their happiness at the workplace also increases. Küçük and Yağıcı (2021) revealed that organizational silence negatively affects happiness in the workplace. Moçoşoğlu and Kaya (2018) reported that a negative relationship was found between organizational silence and organizational happiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this result, it can be said that as the employees' voice increases, their happiness at the workplace also increases. Küçük and Yağıcı (2021) revealed that organizational silence negatively affects happiness in the workplace. Moçoşoğlu and Kaya (2018) reported that a negative relationship was found between organizational silence and organizational happiness.…”
Section: Discussionmentioning
confidence: 99%
“…Employees may have to make a choice to share the ideas, suggestions, and concerns that they have. Employees sometimes opt to share the ideas, suggestions and concerns that they have, while sometimes, they opt to remain silent (Küçük & Yağıcı, 2021). Employees may remain silent thinking that voice behavior is risky and insignificant, that they may lose their jobs, that their interpersonal relationships may deteriorate, and that they may receive negative reactions from their supervisors (Chou et al, 2020;Dedahanov et al, 2022;Duan et al, 2020).…”
Section: Employee Voicementioning
confidence: 99%